Factors Affecting the Financial Performance of Credit Union in Indonesia - Daniel Halomoan Simamora; Willem A. Makaliwe; Eugenia Mardanugraha; Zahra Kemala Nindita Murad (International Journal Labs, 2023)
The research aims to find out a number of things in terms of macro and micro data that affect the condition of the financial performance of Credit union in all provinces in Indonesia both in terms of internal factors and external factors both in terms of microeconomics and macroeconomics. Therefore, the assessment of the financial performance of Credit union throughout Indonesia has an important role to play in terms of profitability ratios which are influenced by a number of variables. Empirical evidence in this study shows that the total assets, the age of the cooperative and the number of members have a positive and significant relationship to the profitability ratio of return on assets of credit union in Indonesia. In addition, Number of Branches, Merger Activities have a negative influence and a significant relationship to the financial performance of credit union. Meanwhile, macroeconomic variables such as provincial GRDP do not have a significant relationship and influence on the activity performance of the return on asset profitability ratio of credit union. This finding has an important role in improving services to credit cooperative members who are SMEs so that they can increase their contribution to the percentage of economic growth.